Talent, strategy, risk : how investors and boards are redefining TSR - McNabb, Bill; Charan, Ram; Carey, Dennis C. (Boston, Massachusetts : Harvard Business Review Press, 2021)
"A playbook for long-term value creation. Balancing the short term and the long term is a perennial struggle, but new developments put boards squarely at the center of this dilemma and in need of guidance. Much of the $14 trillion of assets that firms like Vanguard, BlackRock, and State Street manage is now held in index funds, creating a huge class of permanent institutional investors. These so-called passive investors (unlike activist investors, passive investors don't have power to exit the fund) own almost 60 percent of the Fortune 500-and they have found their voice. Perhaps best exemplified by BlackRock's Larry Fink, these investors are stating in no uncertain terms that simply managing for short-term shareholder profit is not acceptable. In this agenda-setting book, three leaders who have been on the front lines of these changes with boards, management teams, and the investment community challenge leaders to rethink TSR (total shareholder return). Since TSR cannot keep the short and long term in balance, McNabb, Charan, and Carey argue that boards should focus on a different kind of TSR-talent, strategy and risk-because decisions and actions around these factors, more than any others, determine whether or not a company creates long-term value. Offering boards a playbook for managing talent, strategy, and risk, the authors explain how to: analyze the business through the eyes of a shareholder activist, help management take a longer view and communicate it to investors, track execution of long-term plans and goals,keep major risks, such as cyberattacks and sexual harassment, front and center, refresh board composition and create diversity to meet the new challenges. Given the new realities of corporate ownership, boards need to lead for the long term. This authoritative book shows them how"--
Prologue: Changes in the investment community that led to this book -- Introduction: Redefining corporate governance for the long term -- Part one. The new TSR: a framework for long-term management -- Talent rules -- The strategic imperative -- Managing risk -- Part two. Best board practices: Managing the new TSR and long-term value creation -- Creating a capable board -- Redesigning the board's committees -- Diversifying information -- Engaging with investors -- Conclusion: ESG -- the big picture, not just a piece of the puzzle.
Includes index.
Description based on online resource; title from digital title page (viewed on July 15, 2021).
Master record variable field(s) change: 050
Keywords: Boards of directors; Stockholders; Corporate governance; Portfolio management; Risk management; Strategic planning -- Methodology; elektronické knihy; electronic books